IMPLEMENTASI PROGRAM KAWI SMARA (STUDI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KLUNGKUNG DALAM MENINGKATKAN DISIPLIN KEPENDUDUKAN) - Wahyuningtyas, Ni Putu Tirta; Yasintha, Putu Nomy; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT KawiSmara is a public service innovation program carried out by the Department of Population and Civil Registration of Klungkung Regency in the field of marriage certificate services. KawiSmara is a program of giving marriage certificates to the bride during the wedding ceremony. KawiSmara was carried out with the aim of increasing the coverage of ownership of population documents especially marriage certificates. The problem examined in this study is how the implementation of the KawiSmara program in Klungkung Regency covers four sub-districts, so that later it will create a population that is population discipline. Keywords: KawiSmara, Marriage Certificate, Implementation